Desafios e perspectivas na utilização das TICS no contexto educativo de crianças com deficiência visual - Portes, Rutileia Maria de Lima (2013)
This dissertation takes part of researches and discussions that aim to verify the digital inclusion process on Special and Inclusive Education. From the investigation of docent knowledge it aims to understand how are constituted and dimensioned by the practices referring to the resources by which children with visual impairments may access knowledge. The research context was the specialized educational assistance in municipal schools of Uberlândia, Minas Gerais, Brazil, where thirteen students with visual impairments receive a curricular and pedagogical complementation. They are enrolled in nine Basic Education schools in the city. The theoretical framework focuses on information and critical reflections concerning to three main challenges of our time: the Inclusive Education, the digital inclusion and the inclusion of ICTs Information and Communication Technologies in the Education of students with visual impairments. During the course of this dissertation, moved by the characteristic contexts of the present digital age, we proposed to analyze Braille System and the computer with screen reader as resources involved in reading, writing and information access problems, as well in accessing information, knowledge and social interaction. The search method was conducted under a historical and cultural approach, according to Gonzalez Rey s qualitative epistemology. The interviewed subjects culture and identity come into play to determine their knowledge and skills with ICT. We used semistructured interviews as data collection resource. These data were further analyzed under the Content Analysis approach described by Bardin. Data construction resulted in the formulation of categories or analysis axes established from the aspects considered as fundamental in order to include the entire focused reality. From this reality, we discussed the constitution of docent knowledges, the challenges and the possibilities on using the ICT, the didactical aspects and finally, we described the difficulties verified as a result of the inclusion and the exclusion that summit teachers and students. The results reveal knowledges and practices consonant to individual and social culture of teachers, which are characteristic of the historical range we find ourselves, concerning to as the assimilation of digital technologies for education and society.